2013
DOI: 10.1080/09589236.2012.708828
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity and body image: Examining gender variability and the influence of psychological distress in cancer patients

Abstract: Psychosocial factors impacting on the overall quality of life for cancer patients may differ between men and women. This study examined the influence that psychological distress, clinical, and social variables have on sexual activity and body image in adult oncology patients. Symptom data was collected from the Memorial Symptom Assessment Scale (MSAS). Analysis indicated women and patients with reported functional limitations were more likely to be less satisfied with how they looked. The final model showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 64 publications
2
10
0
3
Order By: Relevance
“…In contrast, Campo et al (2017) found a large effect size (d = 1.39) for body image following an abbreviated MSC program in an allfemale sample of cancer survivors. Studies on body image in cancer survivors have found that body image dissatisfaction is higher in women than men (Grant et al, 2011;Krok et al, 2013), consistent with findings in the general population (Algars et al, 2009). Accordingly, it may be that body image concerns were less salient in the current mixed-sex sample than the female samples studied in prior research on self-compassion interventions and body image.…”
Section: Discussionsupporting
confidence: 77%
“…In contrast, Campo et al (2017) found a large effect size (d = 1.39) for body image following an abbreviated MSC program in an allfemale sample of cancer survivors. Studies on body image in cancer survivors have found that body image dissatisfaction is higher in women than men (Grant et al, 2011;Krok et al, 2013), consistent with findings in the general population (Algars et al, 2009). Accordingly, it may be that body image concerns were less salient in the current mixed-sex sample than the female samples studied in prior research on self-compassion interventions and body image.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, studies have shown that symptom distress is closely related to contexts that challenge patients' relationships and activities (Boland et al, ; Potrata, Cavet, Blair, Howe, & Molassiotis, ). Regarding body image, and as corroborated by the literature (Ålgars et al, ; Krok, Baker, & McMillan, ; Woertman & van den Brink, ), the results showed a more negative perception of their body image compared to men. Evolutionary and sociocultural perspectives show that gender is an important determinant of body satisfaction (Ålgars et al, ; Woertman & van den Brink, ), with women reporting higher levels of body dissatisfaction than men, as a result of the rigidity of cultural beauty ideologies (Striegel‐Moore & Franko, ).…”
Section: Discussionsupporting
confidence: 81%
“…Some studies have evaluated sex differences with regard to appearance-related concerns. In one report, female patients and patients with functional limitations were more likely to have distress related to appearance (Krok et al, 2013). Similarly, a separate study tested the sex difference hypothesis and their data revealed that women experienced more distress related to physical changes.…”
Section: Discussionmentioning
confidence: 99%